Feminist Power and its Implications on Uganda’s Malaria Communication - Nakiwala, Aisha Sembatya; Semujju, Brian (Feminist Media Studies, 2019)
This paper examines power and its manifestation in Uganda’s “Stop Malaria Campaign.” It specifically questions the apparent radical feminism, which is conceptualized as a quest for power, and how such excesses drive implementation of the campaign. The paper explains data collected through focus group discussions and key informant interviews using feminist communication theory as informed by the critical ideas of feminism and power. These three ideas help to put into perspective: domination of the campaign by one gender, interpretation of the campaign’s objectives to suit that one gender, and communication methods used in the campaign. Analysis of the above three processes shows that men are the weaker gender in the malaria prevention drive, an idea that has clashed with the existing male chauvinism on which several families still thrive in Africa. A view that radical feminism should be seen as an organized form of power that needs to be checked if Uganda’s malaria communication campaign is to be implemented successfully is herein proposed, along with some solutions to the challenges.
Keywords: Radical feminism,power,Malaria,health communication,communication campaign,Uganda